Influence of Previous Disease-Modifying Drug Exposure on T-Lymphocyte Dynamic in Patients With Multiple Sclerosis Treated With Ocrelizumab. Issue 3 (10th May 2022) - Landi, Doriana; Grimaldi, Alfonso; Bovis, Francesca; Ponzano, Marta; Fantozzi, Roberta; Buttari, Fabio; Signoriello, Elisabetta; Lus, Giacomo; Lucchini, Matteo; Mirabella, Massimiliano; Cellerino, Maria; Inglese, Matilde; et al.
Abstract : Background and Objectives: To investigate the longitudinal dynamic of lymphocyte subsets during treatment with ocrelizumab (OCR) in patients with multiple sclerosis (PwMS). Methods: A multicenter retrospective study was conducted in 161 PwMS starting treatment with OCR grouped in naive (naive, n = 40), switching from fingolimod (FTY, n = 52), and switching from other immunomodulating drugs (other, n = 69). Mean lymphocyte subset (total, CD3 +, CD4 +, CD8 +, CD20 +, and natural killer) counts were analyzed at baseline, 6 months, and 12 months. Rate of lymphocytopenia for each subset was calculated at all time points in all groups. Results: Mean total, CD3 +, and CD4 + counts were significantly different among groups ( p < 0.001) at all time points, whereas CD8 + and CD20 + counts only at baseline ( p = 0.0157; p < 0.001), consistently lower in FTY. After adjustment for baseline values, interaction time*group was not statistically significant ( p > 0.05 for each subset). The odds of lymphopenia were significantly higher among FTY patients compared with naive for total, CD3 +, CD4 +, and CD20 + cells at baseline, for total and CD4 + cells at the sixth month, and for total cells at the 12th month. Discussion: OCR per se exerts a modest depleting effect on T cells that seems rather due to a carryover phenomenon of previous therapies, particularly FTY. These data may help in the overall evaluation of the risk/benefit profile of treatment sequencing.